Targets of peer mistreatment: Do they tell adults? What happens when they do?. (July 2016) - Bauman, Sheri; Meter, Diana J.; Nixon, Charisse; Davis, Stan
Abstract: Using data from 3305 students mistreated by peers two to three times per month or more often, we examined predictors of targets' telling adults at home and school about what happened. Grade, being in special education, having lower socioeconomic status, and physical and forms of social mistreatment were predictors of telling an adult at school. Grade, being in special education, race/ethnicity, experiencing some forms of social mistreatment and specific foci of mistreatment were related to telling an adult at home. We also report how helpful targets found 14 specific adult responses to be (things got better, things stayed the same, things got worse). The helpful responses from teachers most often leading to reports that things got better including showing concern and care for the targeted child. Highlights: We identify predictors of targets' telling adults at school about their plight. We determine which adult responses were most helpful to targets. We identify predictors of targets' ratings of outcomes of adult responses. Students in special education reported less positive outcomes of adult responses. Students who were more distressed rated adult responses as less helpful.